Evaluación de hemoglobina glicosilada y glucosa en pacientes con tratamiento antidiabético, atendidos en Laboratorio Quintanilla - Clínica Peruano Americana, enero - diciembre 2016 - Cueva Bacilio, Corina Cinthia (2017)
The objective of the present study was to evaluate glycosylated hemoglobin and glucose in patients with antidiabetic treatment at the Quintanilla Laboratory - Peruvian American Clinic, January - December 2016, using the data system of the laboratory and clinical records, taking into account the age group (35-70 years) and gender of the patients; the method was descriptive and cross-sectional, and the ethical criteria for the use of information in the report were considered. The sample consisted of 200 patients whose results were: for the 67-patient group (43.8%) of 153 men and 14 patients (29.8%) of women were found in the 55-64 age group of patients with antidiabetic treatment. For glucose, 53 patients (34.6%) of 153 men and 22 patients (46.8) of 47 women had optimal glucose values <130 mg / dL. However, 100 patients (65.4%) of 153 men and 25 patients (53.2%) of 47 women required therapeutic intervention. For glycosylated hemoglobin, 108 patients (70, 6%) of 153 men and 33 patients (70.2%) of 47 women presented optimal values with treatment, however 45 men (29.4%) and 14 women (29.8%) required therapeutic intervention since their value exceed 8% of glycosylated hemoglobin, according to the antidiabetic treatment ten (85.4%) of 123 patients taking metformin presented optimal values with treatment, but 18 patients (14.6%) required therapeutic intervention, 16 patients (66.7%) of 24 patients who had metformin were treated with glucosylated hemoglobin. (33.3%) required therapeutic intervention, 15 patients (57.7%) of 26 taking metformin-glibenclamide presented optimal values with treatment and 11 patients (42.3%) required treatment with glibenclamide. Twenty-one patients (81.5%) of 27 taking metformin-glimepiride presented optimal values with treatment and 5 patients (18.5%) required therapeutic intervention